1997
DOI: 10.1111/j.1440-1738.1997.tb00179.x
|View full text |Cite
|
Sign up to set email alerts
|

The Neftegorsk, Sakhalin Island, earthquake of 27 May 1995

Abstract: Past seismic catastrophes were unknown in Sakhalin Island before 1995 except those suggested from findings of paleoseismodislocations. The first time that dwellers have experienced such a catastrophe in the Sakhalin Island history was on 27 May 1995. The devastating Neftegorsk earthquake occurred in Northern Sakhalin (cp = 52.8" north; h = 143.2' east; H = 18 km; M, = 7.2), killed almost 2000 people in the small city of Neftegorsk, caused damage and destruction of buildings, bridges, railways and roads, breaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…On the basis of earthquake slip data (e.g., the 1995 Neftegorsk earthquake [ Ivashchenko et al , 1997], which indicates a transform boundary in northern Sakhalin), Seno et al [1996] suggested that the Okhotsk Sea Plate currently rotates clockwise about a pole in the northern Okhotsk Sea. This gives a solution that takes into account thrust deformation in southern Sakhalin, which the “extrusion” model [ Jolivet et al , 1994; Worrall et al , 1996] fails to do.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of earthquake slip data (e.g., the 1995 Neftegorsk earthquake [ Ivashchenko et al , 1997], which indicates a transform boundary in northern Sakhalin), Seno et al [1996] suggested that the Okhotsk Sea Plate currently rotates clockwise about a pole in the northern Okhotsk Sea. This gives a solution that takes into account thrust deformation in southern Sakhalin, which the “extrusion” model [ Jolivet et al , 1994; Worrall et al , 1996] fails to do.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Geological map of Sakhalin. Compiled from various sources [ Vereshchagin , 1969; Rozhdestvenskiy , 1982; Kharakhinov et al , 1985; Fournier et al , 1994; Ivashchenko et al , 1997]. (c) Map of major suture zones and tectonostratigraphic units in southeastern Russia.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors suggest that dextral displacement on the Sakhalin‐Hokkaido Shear Zone is the primary reason for the dislocation of the palaeo‐Amur depocentre. Firstly, the Sakhalin‐Hokkaido Shear Zone is seismically active today, as seen in the 1995 Neftegorsk earthquake (Ivashchenko et al ., ). The dextral strike‐slip component of relative motion between these two plates is measured using GPS velocities at 2 mm year −1 (Apel et al ., ), which is consistent with Pleistocene geomorphic slip rates measured from individual fault strands of the Sakhalin‐Hokkaido Shear Zone (Nicholson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The continuous seismic background and occurrence of strong earthquakes demonstrate that tectonic processes are still ongoing in the crust below Sakhalin and the surrounding offshore areas [e.g., Zlobin, 2005;Tichonov and Lomtev, 2014]. The strongest recorded earthquake in this region, with a magnitude of M W 7.6, occurred on 28 May 1995 in the northern part of Sakhalin [e.g., Rogozhin, 1996;Ivashchenko et al, 1997]. In only 17 s, it caused sufficient damage to completely destroy the city of Neftegorsk and kill 2040 people (almost two-thirds of the city's population).…”
Section: Tectonics Seismic Activity and Geothermal Manifestationsmentioning
confidence: 99%
“…Many authors have suggested that the north-south-oriented lineament throughout Hokkaido and Sakhalin represents a fault zone with a predominant dextral strike-slip component [e.g., Fournier et al, 1994]. The mechanisms of pure strike-slip displacement during the catastrophic Neftegorsk earthquake with a magnitude of M W 7.6, occurred on 28 May 1995 in the northern part of Sakhalin seem to support this model [e.g., Rogozhin, 1996;Ivashchenko et al, 1997;Katsumata et al, 2004]. However, a series of recent earthquakes in the southern part of Sakhalin, including the M W 6.2 Nevelsk earthquake, reveal almost pure thrust deformation [Konovalov et al, 2015].…”
Section: Introductionmentioning
confidence: 99%